Agama Adam dan Peribadatan dalam Ajaran Samin - Moh Rosyid (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2020)
This article to description Adam religion and worship Samin community in Region Kudus Central Java. This research data was descriptive analysis a by interview, participatory observation, and literature review. Data collection was analysed using a qualitative descriptive approach. Data collection was observation and literature. Public research aim gets rid of stigma as a dissident, ateis, poor. By understanding about Samin realize tolerance. Result, word ‘Adam’ for Samin is prime god creatures. Religious Adam teachings semedi, pray, fasting, and manifested in life wisdom. A place of worship in home (sanggar pamujan), best time of worship at midnight time. Obedience and disobedience dependents personally. Adam religions by government is indigenous religions. The teachings by oral traditions. Basic problem fased Samin community is poor not be a farmer anymore especially young children, not united and disagree between Samin the impact of understanding the teachings said inherit need a middle ground between Samin the attempts to argue for government watch out for.